Employee engagement, telecommuting propensity, and employee performance in the virtual workplace - Hangwani Ravhudzulo; Chukuakadibia Eresia-Eke (Cogent Business & Management, 2024)
The COVID-19 pandemic catalysed a monumental shift in the traditional workplace, compelling organisations worldwide to rapidly embrace telecommuting. This unplanned experiment has challenged assumptions about productivity and collaboration, while raising crucial questions about the intricate interplay between employee engagement, telecommuting propensity, and employee performance. This study aims to illuminate the dynamics underpinning the virtual workplace, offering insights to inform effective strategies for optimising employee performance in the evolving work landscape of the South African ICT sector. Leveraging the employee engagement theory, social exchange theory, and the Triarchy Model of employee performance, the study examines the relationships between these pivotal constructs. The population for this study is employees working in South Africa's ICT sector. Data collected from 478 respondents was analysed through structural equation modelling. The study discovers direct relationships among the constructs. Employee engagement is positively associated with employee performance, and telecommuting propensity. However, the study found no relationship between telecommuting propensity and employee performance. The research findings suggest that the studied employees working in the South African ICT sector exhibit heightened engagement and performance when telecommuting, despite telecommuting propensity not being a direct determinant of performance. These insights offer valuable implications for organisational strategies and practices to foster employee engagement, productivity, and overall effectiveness in the evolving work landscape.
Keywords: 650; Covid-19 pandemic; employee engagement; employee performance; evolving work landscape; ICT sector; telecommuting propensity; virtual workplace